The role of public administration in quality improvement of specialists’ vocational training - Gren, L. M. (My University, 2020)
Vocation-and-technical training is considered in the article as one of the main directions that enhances development of industry branches of the present regional complex of Ukraine; the results of a test research concerning the estimation of the vocation-and-technical training system’s efficiency are given; it is proved that the vocation-and-technical training system’s regulating depends on the state regulatory institutions of the municipal, regional, and allstate central power bodies that in their unity form a certain mechanism of state regulation of the vocation-and-technical training system’s development.
Keywords: state management; state management mechanism; vocation-and-technical training; qualified workers